Implementation of Instructional System Development Education Method in Wingdik 600/Pembekalanq - Prahardanto, Agung; Akim; Djuyandi, Yusa (International Journal of Science and Society, 2024)
To build and develop the air force power to ensure preparedness in defending the country's sovereignty, currently the Indonesian government through the Ministry of Defense is procuring many new defense equipment for the Indonesian Air Force. In preparing the mandate of the new defense equipment, personnel with the ability and expertise are needed to be able to mann, operate, and maintain new equipment. For the preparation of these personnel, one of them was carried out at Wingdik 600/Debriefing which carried out education for the debriefing of personnel as one of the supporting components in the information of new defense equipment in the field of maintenance. In the implementation of education to produce personnel to support existing defense equipment with the Instructional System Development (ISD) education method. ISD directs students to gain the experience and expertise needed to carry out tasks by providing the knowledge, abilities, and expertise needed to carry out tasks. The implementation of ISD education held in Wingdik 600/Briefing is carried out using 10 educational components as guidelines in the implementation of education held. From the results of interviews with informants and also from secondary data, it was obtained that the implementation of education with ISD still needs to be improved by fulfilling educational components in the form of curriculum, teaching packages, instructors, education personnel, students, alin/alongin, teaching methods, educational evaluation, educational facilities and budgets. To obtain educational results that are in accordance with the needs of the Indonesian Air Force, to become a respected Indonesian Air Force, personnel who have abilities and expertise in accordance with their field of duty and are able to navigate the available defense equipment well.